2001
DOI: 10.1070/rc2001v070n01abeh000578
|View full text |Cite
|
Sign up to set email alerts
|

Rigid-rod poly(benzobisazoles) and molecular composites based on them

Abstract: Cylindrical pipes are widely used in industries such as nuclear power plants and micro total analysis systems (mTAS). Measuring the flow rate of fluid in such pipes is critical. Ultrasonic flowmeters are noncontact, nondestructive, and easy-to-use devices, and are therefore widely used. However, typical bulk-wave-based ultrasonic flowmeters cannot be used for pipes narrower than the wavelength of bulk waves. For such pipes, we are currently developing a ''guide wave flowmeter'' that uses guide waves instead of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Molecular composites on the basis of blends of aromatic polyamides (aramids), that is, PBA and PPTA, with aliphatic polyamide PA-6 were thoroughly studied first of all. 5,6 In USSR, works on modification of aramid fibers by aliphatic polyamids started after first publications about blends of rigid-chain and flexible-chain polyamides. Mixing polymers were carried out usually in the common solvent -sulfuric acid (H 2 SO 4 ).…”
Section: Molecular Compositesmentioning
confidence: 99%
“…Molecular composites on the basis of blends of aromatic polyamides (aramids), that is, PBA and PPTA, with aliphatic polyamide PA-6 were thoroughly studied first of all. 5,6 In USSR, works on modification of aramid fibers by aliphatic polyamids started after first publications about blends of rigid-chain and flexible-chain polyamides. Mixing polymers were carried out usually in the common solvent -sulfuric acid (H 2 SO 4 ).…”
Section: Molecular Compositesmentioning
confidence: 99%
“…The data on the molecular composites based on rigid-chain polybenzobisazoles have been generalised in a review. 109 It is reported that these composites are the most promising materials for those fields where low mass, high strength, thermal and chemical stability, and transparency with respect to radio waves are critical. Publications of the past decade consider miscellaneous properties of ring ± chain polyheteroarylenes and various aspects of their applications in diverse branches of modern engineering, such as antifriction and self-lubricating plastics, composite materials, films, membrane and foamed materials, fibres, wave guides, adhesives, photoresists, etc.…”
Section: Variations Of Chemical Structures Of Monomersmentioning
confidence: 99%
“…Fused aromatic−heterocyclic polymers such as polybenzoxazoles (PBO), polybenzothiazoles (PBT), and polybenzimidazoles (PBI) continue to attract R & D interest mainly because of their high-temperature capabilities as well as their attractive mechanical, optical, and electronic properties, , more recently because of their potential for high-temperature fuel cell applications . However, they have limited processability due to their insoluble nature and high softening temperature, which is generally above their degradation temperature.…”
Section: Introductionmentioning
confidence: 99%